2022
DOI: 10.3390/ijms23063185
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of PD-1 in Circulating CD4+ and CD8+ Tregs Is an Early Feature of RRMS

Abstract: Altered regulatory T cell (Treg) function could contribute to MS. The expression of activating and inhibitory receptors influences the activity of Tregs. Our aim was to investigate T cell phenotypes in relapsing–remitting MS (RRMS) patients at an early phase of the disease. We examined the influence of demographic parameters on the distribution of CD4+ and CD8+ T cell subclasses by generalized linear modeling. We also studied the expression of the following markers—CTLA-4, GITR, PD-1, FoxP3, Helios, CD28, CD62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Focusing on DCs/Tregs that are stimulated by MBPs, T cells expressing PD-1 and APC expressing PD-L1 in the peripheral blood of patients with acute MS were prominently increased compared with those of remitted patients with MS ( 68 ). A recent study also showed that the expression of PD-1 on the surface of CD4 + and CD8 + Tregs was reduced in patients with RRMS ( 69 ). Taken together, these studies suggested that the DC- or Treg cell-related PD-L1/PD-1 axis is involved in the occurrence and development of MS.…”
Section: Bidirectional Dc-treg Cell Crosstalk In Ms Patients and Eae ...mentioning
confidence: 96%
See 1 more Smart Citation
“…Focusing on DCs/Tregs that are stimulated by MBPs, T cells expressing PD-1 and APC expressing PD-L1 in the peripheral blood of patients with acute MS were prominently increased compared with those of remitted patients with MS ( 68 ). A recent study also showed that the expression of PD-1 on the surface of CD4 + and CD8 + Tregs was reduced in patients with RRMS ( 69 ). Taken together, these studies suggested that the DC- or Treg cell-related PD-L1/PD-1 axis is involved in the occurrence and development of MS.…”
Section: Bidirectional Dc-treg Cell Crosstalk In Ms Patients and Eae ...mentioning
confidence: 96%
“…The binding of GITRL on the DC surface and the corresponding receptor (i.e., GITR) on the Treg cell surface can improve the sensitivity of Treg precursor cells to IL-2 and provide co-stimulatory signals for Treg cell proliferation ( 134 , 135 ). A recent study showed that the expression of GITRs on the surface of CD4 + and CD8 + Tregs was decreased in RRMS individuals ( 69 ). This might be one of the reasons that DC-Treg cell crosstalk is destroyed in MS patients, which limits the proliferation of DC-dependent Tregs.…”
Section: Unidirectional Regulation Of Tregs By Dcs In Ms/eaementioning
confidence: 99%
“…Treg are a heterogeneous population [68]. Most Treg are CD4 + but some are CD8 + and these CD8 + Treg may play a critical role in susceptibility to some autoimmune diseases, such as multiple sclerosis [69]. Most Treg develop in the thymus and these Treg are called natural Treg.…”
Section: Regulation Of the Immune Responsementioning
confidence: 99%
“…(MS) is considered to be the most common neurological disease in young adults, affecting more than 2.5 million people worldwide (Att eld et al 2022). It is described by continuous in ammatory activity within the CNS, giving rise to tissue damage that results in brain and spinal cord atrophy and irreversible neurological disability (Machcińska et al 2022).…”
Section: Introductionmentioning
confidence: 99%